The Mechanism in which Sjogren's Syndrome Contributes to The Onset of Erectile Dysfunction - Ria Margiana; Azlansyah Azlansyah (Universitas Airlangga, 2023)
Sjogren's Syndrome is an autoimmune disorder characterized by the loss of salivary and lacrimal glands, resulting in dry mouth and eyes. Erectile dysfunction (ED) is a prevalent complaint among people with Sjogren's Disease, however the underlying mpoiechanism is not yet known. The purpose of this article is to examine the mechanism through which Sjogren's Disease causes ED and to identify potential therapies. Using MEDLINE, EMBASE, and the Cochrane Library databases, a systematic review was done. Papers investigating the link between Sjogren's Syndrome and ED published between 1990 and 2021 were included in the study. The review paper discusses a number of potential mechanisms for the association between Sjogren's Disease and ED. They include low levels of testosterone, endothelial dysfunction, autonomic neuropathy, and psychosocial issues. The article also discusses potential treatments for ED caused by Sjogren's Disease, including inhibitors of phosphodiesterase type 5, testosterone replacement therapy, and psychological counseling. The research implies a connection between Sjogren's Disease and ED, although the underlying mechanisms remain unknown. It is necessary to conduct additional studies to better comprehend the relationship and develop targeted remedies.